CORONAVIRUS DISEASE 2019 (COVID-19) DARI PERSPEKTIF DERMATOLOGI - Sitaresmi, Adya; Setyowatie, Lita (Jurnal Klinik dan Riset Kesehatan, 2021)
Coronavirus Disease 2019 (COVID-19) is a new disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection. Common clinical manifestations are respiratory system disorders. However, COVID-19 can also manifest as extrapulmonary symptoms, one of which is dermatology. The exact mechanism of COVID-19 cutaneous manifestations is still not fully understood, but is suspected to be caused by the direct effects of the virus on keratinocyte, excessive immune response, or drugs used to treat COVID-19. Cutaneous manifestations of COVID-19 can be divided into five groups, namely pseudo-chilblains, vesicular, urticaria, erythematous maculopapular, and vascular lesions. Erythematous maculopapular (44.18%) and chilblains (19.72%) are the most common lesions. Vesicular and vascular lesions are less common. Chilblains lesions are usually found before or together with the onset of other COVID-19 symptoms, and often appear in close contact or asymptomatic patients, so early recognition of it can be used to detect the presence of COVID-19.